Notch signaling in the pathologic adult brain - Mathieu, Patricia Andrea (2013)
Along the entire lifetime, Notch is actively involved in dynamic changes in the cellular architecture and function of the nervous system. It controls neurogenesis, the growth of axons and dendrites, synaptic plasticity, and ultimately neuronal death. The specific roles of Notch in adult brain plasticity and neurological disorders have begun to be unraveled in recent years, and pieces of experimental evidence suggest that Notch is operative in diverse brain pathologies including tumorigenesis, stroke, and neurological disorders such as Alzheimer's disease, Down syndrome, and multiple sclerosis. In this review, we will cover the recent findings of Notch signaling and neural dysfunction in adult human brain and discuss its relevance in the pathogenesis of diseases of the central nervous system.